Gambaran Perilaku Pemberantasan Sarang Nyamuk (PSN) pada Ibu Rumah Tangga di Wilayah Kerja Puskesmas Nagi Kabupaten Flores Timur - Triwibowo Saputra Kopong Daten; Afrona E. L. Takaeb; Helga J. N. Ndun (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the infectious diseases that is a health problem at the Nagi Health Center, East Flores Regency. This disease is caused by the dengue virus (arbovirus) which is transmitted through the bite of the female Aedes aegypti mosquito. This study aims to determine the description of PSN behavior in housewives in the Nagi Health Center work area of ​​East Flores Regency. This type of research is qualitative with indepth interview techniques. The informants interviewed were seven housewives. The results of this study indicate that the level of knowledge and understanding of housewives about PSN is still focused on preventing adult mosquitoes. Meanwhile, only a small number of informants understand that PSN activities also include efforts to eliminate and overcome mosquito larvae. Some PSN actions that are carried out well by most informants include closing the landfill and using mosquito nets. Other PSN actions that are not carried out well by most informants include draining the landfill, waste processing, using abate, using antimosquito lotion and the habit of hanging clothes carelessly. Health workers need to increase counseling regarding PSN as an effort to prevent DHF.